Political Communication Capacity Building Young Cadres of DPD Golkar Party Bandung District - Kurniawati, Nia (ASEAN Journal of Empowering Community, 2022)
This PKM activity aims to improve the political communication skills of the Young Cadres of DPD Golkar Party Bandung Regency through political education. Political education is carried out through technical guidance with material on "Empowering Political Communication" and the practice of effective and efficient political communication processes through speeches from each participant. From this activity, it is expected that young party cadres can appear to develop their potential in the party.